2004
DOI: 10.1007/s00464-003-9029-5
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic management of common bile duct stones

Abstract: When correct indications and surgical expertise are observed, simultaneous laparoscopic management of common bile duct stones represents a safe and minimally invasive alternative to a two-procedure approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
19
0
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 29 publications
2
19
0
3
Order By: Relevance
“…Published reports on the laparoscopic treatment of choledocholithiasis include both cohort studies and individual series [167][168][169][170][171][172][173][174][175][176]. Switching to open surgery occurred in 1.4-13% of procedures [167][168][169][170][171][172][173][174][175][176], and transcystic stone removal was performed more frequently than choledochotomy, with the former being performed in 60-70% of cases [167][168][169][170][171][172][173][174][175][176]. All of these reports found that laparoscopic one-stage removal of common bile duct stones is noninferior to two-stage removal using a peroral endoscope and that laparoscopic surgery can be performed in most cases of choledocholithiasis.…”
Section: Commentarymentioning
confidence: 99%
“…Published reports on the laparoscopic treatment of choledocholithiasis include both cohort studies and individual series [167][168][169][170][171][172][173][174][175][176]. Switching to open surgery occurred in 1.4-13% of procedures [167][168][169][170][171][172][173][174][175][176], and transcystic stone removal was performed more frequently than choledochotomy, with the former being performed in 60-70% of cases [167][168][169][170][171][172][173][174][175][176]. All of these reports found that laparoscopic one-stage removal of common bile duct stones is noninferior to two-stage removal using a peroral endoscope and that laparoscopic surgery can be performed in most cases of choledocholithiasis.…”
Section: Commentarymentioning
confidence: 99%
“…Unter Einhaltung dieser Vorgaben beträgt die perioperative Morbidität für die laparoskopische Choledochusrevision zwischen 3-20%, die Mortalität bis zu 1,7%. [25]. Voraussetzung für den anschließenden sicheren Verschluss der Choledochotomie ist die diffizile Beherrschung 7 laparoskopischer Verschluss-und Knotentechniken.…”
Section: Laparoskopische Choledochusrevisionunclassified
“…Die aktuelle Entwicklung weist international allerdings in eine andere Richtung. In der Literatur wird zunehmend über große Serien von laparoskopischen Choledochusrevisionen berichtet [7,8,21,28,38].…”
Section: Introductionunclassified
“…Falls dies der Fall ist, kann die Choledochotomie mit gleicher Sicherheit wie bei der offenen Revision verschlossen werden. In erfahrenen Zentren kann mit dieser Technik bei 90-95% der Patienten auf laparoskopischem Wege eine Steinfreiheit des Gallengangssystems erreicht werden[8,21,28]. Dies entspricht den Zahlen, die früher bei der offenen Gallengangsrevision berichtet wurden.…”
unclassified